A contribution to the knowledge of the butterfly fauna (Lepidoptera: Rhopalocera) of the Cerkljansko Idrijsko region, west Slovenia, with notes on their vertical distribution - Rudi Verovnik (Natura Sloveniae)
Results of the fieldwork carried out by a lepidopterology group at the Student Research Camp Cerkno '00 are presented. Altogether, 77 butterfly species were recorded between June 26th and July 3rd 2000 at 38 localities, including individual observations. The most interesting discovery was the presence of Maculinea telejus Bergstr. in the Bača valley just south of the Julian Alps. Among typically alpine species, Aricia artaxerxes F. was recorded exclusively at lower altitudes, whereas its colline sister species A. agestis Schiff. was found near the top of Mt. Črna prst at an altitude around 1800 m. The highest diversity of butterfly species and habitat types was observed between 500 and 750 m. Despite the geographical heterogeneity, only few parts of the region have escaped intensive exploration and could be considered important habitats for the threatened butterfly species in Slovenia. The highest conservation value should be acknowledged to the presence of the relatively large and probably interconnected subpopulations of Maculinea arion L. in the eastern part of the region.